Effectiveness of Village Fund Use in Improving Community Welfare in Lalabata Village, Barru Regency - Askar, Asrul Askar; Herman H; Rifdan; Haerul; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2025)
In addition to analyzing the supporting and impeding elements, the purpose of this study is to determine how successfully Village Fund utilization improves community welfare in Lalabata Village, Barru Regency. The study used a case study methodology in conjunction with a qualitative approach. Observation, interviews, and documentation were used to gather data, which were then analyzed using the steps of data condensation, presentation, and conclusion drawing. The results show that Lalabata Village's usage of village funds is thought to be fairly successful. This effectiveness is reflected in the implementation of priority programs, including the construction of farm roads, drainage systems, bridges, wells, market and tourism development, stunting prevention, and social assistance. These programs were designed and implemented participatively through village deliberations, ensuring that community needs were well accommodated. The village government also applied principles of transparency and accountability. Reporting was carried out through public billboards and village forums, while involving the community in planning, implementation, and monitoring processes. Capacity building for village officials and the provision of supporting facilities further strengthened program sustainability. However, several obstacles remain, including delays in fund disbursement, inadequate infrastructure, extreme weather conditions, and unresolved land grant processes. These challenges affected the smooth execution of some development activities. On the other hand, the efficient administration of village funds was made possible by auxiliary elements such as government policy, information system use, and village official training. Although technical and administrative improvements are still required, Lalabata Village's Village Funds management is generally seen as being fairly effective in enhancing community welfare.